Onion maggot (Delia antiqua): A destructive pest of onion - Sable, P A; Chandaragi, M K (Indian Horticulture, 2021)
Onion is a high valued bulb crop cultivated commercially all over India for its medicinal, aromatic and food plant since ancient times. It is also called as Queen of Kitchen due to in unique characters like aroma, flavor, and taste. It is widely used throughout the year in curry preparation and in the form of processed foods. India is one of the major onions producing country. The total onion production of India is 228.19 lakh tonnes out of which share of kharif onion is 48.41 lakh tonnes, late kharif onion 21.50 and rabi onion 158.28 lakh tonnes. The major onion producing states are Maharashtra, Madhya Pradesh, Karnataka, Rajasthan, Bihar, Gujarat, Andhra Pradesh, Haryana, West Bengal and Uttar Pradesh in the country. These states account for almost 90% of the total onion production in the country. Maharashtra ranks first in onion production (8047 thousands to nnes) with a share of 35.26% in 2018-19. In India there are several factors like biotic (Insect pests and diseases) and physiological constraints which affect the yield of onion adversely and reduce productivity.